Animal-Computer Interaction (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
We are excited to present this Special Issue, which shares new ideas and developments in the field of Animal–Computer Interaction, including those that advance scientific knowledge about animals, enhance connections between species, improve the stewardship of animals in human care and articulate the design of systems that offer greater autonomy to other species. This collection of articles features research with mammals, birds, fish, reptiles and amphibians, including wild, farmed, zoo-housed and working contexts. The diversity of approaches illustrates how technology can be used as a tool to support humans working with both free-roaming and managed animals, facilitating initiatives in conservation, welfare and enrichment. This demonstrates the potential for interesting and insightful collaborations between animal experts and technologists, working together to create an equitable and sustainable future for all species.